MOLECULAR ANALYSIS AND BIODIVERSITY OF METAZOAN PARASITES OF THE YELLOWTAIL LAMBARI, ASTYANAXAFF. BIMACULATUS (TELEOSTEI, CHARACIDAE), IN LOWER SAN FRANCISCO, NORTHEASTERN BRAZIL - Pedroza de Vasconcelos, Alessa Caroline (2013)
The difficulty in identifying some species of Lambaris comes from very similar phenotypic feature that often result from hybridization. The parasites can be indicative of various aspects of the biology of their hosts, including phylogeny, because some groups of parasites may have host specificity. The objective was to evaluate the genetic diversity and parasitology of the fish Astyanaxaff.bimaculatus. in ponds and streams adjacent to fish farms located in the Lower São Francisco, Sergipe, Brazil. The specimens were collected in the municipalities of Propriá and Neópolis and necropsied in the search for metazoan parasites. Sections of muscle tissue were taken for DNAextraction. The samples were subjected to PCR and electrophoresis with the products of the reactions. Subsequent cluster analysis was performed. Atotal of 102 fish were infected with Lernaeacyprinaceaand Dolopssp. on the body surface, Urocleidoidessp. and metacercariae of Echinostomatidae in gills, Prosthenhysteraobesain the gallbladder, Diplostomidae type Neascusin the swim bladder and the nematodes Procamallanushilariiand Rabdochonasp. in the gut. The genomic material of Astyanaxaff. bimaculatuswere evaluated with by origin: 34.3% from Propriá and 65.7% from Neopolis. Approximately 41% of the fish collected showed a homogeneous electrophoretic profile by using the primer CCCGTAGCAC. Among the specimens from Propriá, the genomic material presented electrophoretic profile with bands 800pb and >800pb. The last profile was more prevalent in hosts with Echinostomatidae in gills. Cluster analysis yielded a phylogenetic tree with two branches / groups, independent of the place of origin. However, it was homogeneous with respect to the expression of the character susceptibility / resistance to parasitic infection. These strategies can help in molecular taxonomic identification of Astyanaxaff. bimaculatus, which is difficult because of the great similarity in external morphology.